2020
DOI: 10.1371/journal.pone.0229546
|View full text |Cite
|
Sign up to set email alerts
|

Consumer preference to utilise a mobile health app: A stated preference experiment

Abstract: BackgroundOne prominent barrier faced by healthcare consumers when accessing health services is a common requirement to complete repetitive, inefficient paper-based documentation at multiple registration sites. Digital innovation has a potential role to reduce the burden in this area, through the collection and sharing of data between healthcare providers. While there is growing evidence for digital innovations to potentially improve the effectiveness and efficiency of health systems, there is less information… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 37 publications
(31 reference statements)
1
19
0
1
Order By: Relevance
“…Some assessment criteria that may facilitate the evaluation of the value domain were identified, such as questions related to an app’s usefulness in improving patients’ quality of life, 20 improve monitoring and management of disease, 20 , 21 and facilitate healthcare service appointments. 22 …”
Section: Resultsmentioning
confidence: 99%
“…Some assessment criteria that may facilitate the evaluation of the value domain were identified, such as questions related to an app’s usefulness in improving patients’ quality of life, 20 improve monitoring and management of disease, 20 , 21 and facilitate healthcare service appointments. 22 …”
Section: Resultsmentioning
confidence: 99%
“…Perceptions of functionality, performance, trustworthiness, ease of use (e.g., interface, time required to learn etc. ), and certain privacy concerns that are influential in usage [ 31 ] may be overcome by application developers through the careful design of mobile apps and communication in mobile marketplaces [ 32 ]. For instance, it has been shown that informational content, organizational attributes, technology-related features, and user control factors influence the trustworthiness of m-health applications [ 33 ].…”
Section: Background and Related Workmentioning
confidence: 99%
“…We segmented literature into three preference-elicitation categories based on the preference study design: (I) experimental preference methods (DCE, conjoint analysis, (60), and one used a take-it-or leave conjoint analysis (62).…”
Section: Preference Elicitation Approachesmentioning
confidence: 99%
“…Sub-group and heterogeneity analysis conducted in many studies revealed that demographic characteristics such as age (47,54,62,65,66,70,71,74,78,86,87,97,101), race (60,102), gender (51,62,86,97), education (62,86,87,101), income (46,70) and proximity to care (46,79) were associated with patient preferences for HIT. Younger patients and higher income patients generally placed higher utility on HIT services.…”
Section: Preferences For Hit Vary Based On Patient Characteristicsmentioning
confidence: 99%